2014
DOI: 10.1002/bjs.9536
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal injury to liver, pancreas and kidney during irreversible electroporation in an in vivo experimental model

Abstract: IRE can generate thermal energy, and even thermal injury, based on tissue type, probe exposure lengths, pulse lengths and proximity to metal. Awareness of probe placement regarding proximity to critical structures as well as probe exposure length and pulse length are necessary to ensure safety and prevent thermal injury. A probe exposure of 2·5 cm or less for liver IRE, and 1·5 cm or less for pancreas, with maximum pulse length of 90 µs will result in safe and non-thermal energy delivery with spacing of 1·5-2·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 29 publications
4
81
1
1
Order By: Relevance
“…Other studies have concluded that IRE does not produce significant thermal energy, at least when using settings most commonly applied in clinical treatment, but it has been shown that the presence of a metallic stent could increase the risk of producing thermal injuries, due to metal conductivity[56,68]. This aspect is therefore fundamental to keep in mind when treating patients who are carrying a biliary metallic stent for jaundice palliation.…”
Section: Techniques and Resultsmentioning
confidence: 99%
“…Other studies have concluded that IRE does not produce significant thermal energy, at least when using settings most commonly applied in clinical treatment, but it has been shown that the presence of a metallic stent could increase the risk of producing thermal injuries, due to metal conductivity[56,68]. This aspect is therefore fundamental to keep in mind when treating patients who are carrying a biliary metallic stent for jaundice palliation.…”
Section: Techniques and Resultsmentioning
confidence: 99%
“…However, to perform either the percutaneous approach or the open technique we need dedicated experienced interventional radiologists and these approaches might be done in a high-volume center of pancreatic surgery. The percutaneous approach, as well as the open one, is inapplicable in case of metallic biliary or duodenal stents (at least without removing them before performing IRE), because the presence of the metal that could transfer thermal energy causing injuries [35]. This aspect, together with suffering from cardiac arrhythmias (or in patients with pacemakers), represents an absolute contraindication to IRE.…”
Section: Discussionmentioning
confidence: 99%
“…Biological tissues are by nature resistors and the Joule heating cannot therefore be zero. The rise in temperature caused by electroporation in an experimental study was up to 60 • C [6]. This level of hyperthermia however only occurs in the immediate proximity to the electrodes (fine, 19 G straight and not cooled) and only for a few tens of s. Ultimately the ''actual'' thermal effect of electroporation is very limited and only affects tissues located in a radius of a few millimeters around the electrodes.…”
Section: Electroporation: When Thermo-ablation Is Too Riskymentioning
confidence: 96%